2016
DOI: 10.1093/protein/gzw013
|View full text |Cite
|
Sign up to set email alerts
|

Improved prediction of antibody VL–VHorientation

Abstract: Antibodies are important immune molecules with high commercial value and therapeutic interest because of their ability to bind diverse antigens. Computational prediction of antibody structure can quickly reveal valuable information about the nature of these antigen-binding interactions, but only if the models are of sufficient quality. To achieve high model quality during complementaritydetermining region (CDR) structural prediction, one must account for the V L -V H orientation. We developed a novel four-metr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 17 publications
0
83
0
Order By: Relevance
“…In AMA-II, we found that non-native V L –V H orientations can lead to explicit interactions between the light chain and the CDR H3 loop that are indistinguishable from native interactions 5 . Using multiple V L –V H orientation templates 27 allows broader exploration of conformational space, sampling more low-scoring wells. Models generated from at least three different templates should be used to maximize the chance of capturing the native V L –V H orientation.…”
Section: Anticipated Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In AMA-II, we found that non-native V L –V H orientations can lead to explicit interactions between the light chain and the CDR H3 loop that are indistinguishable from native interactions 5 . Using multiple V L –V H orientation templates 27 allows broader exploration of conformational space, sampling more low-scoring wells. Models generated from at least three different templates should be used to maximize the chance of capturing the native V L –V H orientation.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…The two plots show distributions of the Heavy Opening Angle 27 as obtained by plot_LHOC.py for two different antibodies. The 10 distinct light-heavy orientation templates are represented by the circles.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations